Conversion of microalgal lipids to biodiesel using chromium-aluminum mixed oxide as a heterogeneous solid acid catalyst - Guldhe A.; Moura C.V.R.; Singh P.; Rawat I.; Moura E.M.; Sharma Y.; Bux F. (My University, 2025)
Heterogeneous solid acid catalyzed conversion of microalgal lipids to biodiesel is a scarcely studied area. In this study chromium-aluminum mixed oxide catalyst was investigated for catalytic conversion of microalgal lipids to biodiesel. Lipids from Scenedesmus obliquus grown in an open raceway pond (3000L) was used as feedstock. Reaction variables such as temperature, methanol to oil molar ratio and catalyst amount were optimized using response surface methodology. FAME conversion of 98.28% was achieved using chromium-aluminum catalyst at 80 °C, with methanol to oil molar ratio of 20:1 and catalyst amount of 15%. Catalytic efficiency of this heterogeneous solid acid catalyst was compared to a homogeneous acid catalyst (sulfuric acid). Chromium-aluminum mixed oxide catalyst can be effectively used for 4 batches of conversion reactions without significant loss in its activity. © 2016 Elsevier Ltd